Close female friendships and knowledge of recommended abortion methods in Nigeria and the Democratic Republic of the Congo among a representative sample of reproductive-aged women - Anjur-Dietrich, Selena P.; Rhoades, Alice; Akilimali, Pierre Z.; OlaOlorun, Funmilola M.; Omoluabi, Elizabeth; Bell, Suzanne O. (Frontiers in Reproductive Health, 2024)
IntroductionThere is a high incidence of unsafe abortion among women in Nigeria and the DRC. Low knowledge of recommended abortion methods [i.e., surgical and medication abortion (MA) pills] is a barrier for women accessing safe abortions. Women often rely on friends for information about abortion methods. Understanding characteristics of women with knowledge of recommended abortion methods, and MA specifically, and how it is influenced by close female friendships may help identify women most at risk of relying on unsafe abortion.MethodsWe used survey data from Performance Monitoring for Action from 11,106 women of reproductive age in Nigeria (April–May 2018) and 3,697 women in Kinshasa and Kongo Central, DRC, (December 2021–April 2022) to produce representative estimates of knowledge of abortion methods at the national and province levels, respectively. We performed bivariate and multivariate logistic regression to determine which characteristics were independently associated with knowing a recommended abortion method, with knowing of MA pills specifically, and to assess our hypothesis that having at least one female confidante would increase one's odds of knowing about these methods.ResultsA minority (26.9%) of women in Nigeria and the majority in Kinshasa (76.7%) and Kongo Central (58.1%) reported having knowledge of at least one recommended abortion method, while knowledge of MA pills was low in all sites. Having at least one close female confidante was associated with increased odds of knowing a recommend abortion method in Nigeria (aOR = 1.50, 95% CI 1.25–1.79) and in Kongo Central (aOR = 2.66, 95% CI 1.40–5.40), and with increased odds of knowing about MA specifically in Kinshasa (aOR = 1.44, 95% CI 1.08–1.93) and Kongo Central (aOR = 3.61, 95% CI 1.28–10.22), but not Nigeria.DiscussionIn legally restrictive contexts where knowledge of recommended abortion methods (particularly medication abortion) is low, having close female friends is related to increased knowledge of recommended abortion methods.